How Profitability Moderates the Impact of Enterprise Risk Management, Intellectual Capital, and Sustainability Reporting on Firm Value? - Sasa Saefulrohman Suratman; Mochammad Ridwan; Erik Syawal Alghifari; Ilham Adi Handoyo (Faculty of Economics, Universitas Sriwijaya, 2023)
This research tries to test the influence of enterprise risk management, intellectual capital, and sustainability reports on firm value, with a moderating effect on profitability. Data from 16 food and beverage sub-sector companies listed on the IDX has been taken from 2021 to 2022 and analysed using a panel data regression approach and model robustness testing using the robust least squares analysis method. The research results show the positive effect of enterprise risk management and intellectual capital on firm value, as well as the negative effect of sustainability reports on firm value. The moderation results show that the interaction of profitability weakens the positive effect of enterprise risk management and intellectual capital on firm value. The results also reveal that profitability strengthens the negative influence of sustainability reports on firm value. This paper discusses the implications of this research for existing literature, practitioners, and policymakers.